2007
DOI: 10.1186/1472-6882-7-24
|View full text |Cite
|
Sign up to set email alerts
|

Potentials of leaves of Aspilia africana (Compositae) in wound care: an experimental evaluation

Abstract: Background: The potentials of the leaves of the haemorrhage plant, Aspilia africana C. D Adams (Compositae) in wound care was evaluated using experimental models. A. africana, which is widespread in Africa, is used in traditional medicine to stop bleeding from wounds, clean the surfaces of sores, in the treatment of rheumatic pains, bee and scorpion stings and for removal of opacities and foreign bodies from the eyes. The present study was undertaken to evaluate the potentials for use of leaves of this plant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
68
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 14 publications
5
68
0
3
Order By: Relevance
“…More so, saponnins have been reported to have precipitating and coagulative properties. The result of this study coupled with increased mean platelet volume (MPV) in the aqueous extract and results from previous studies [12][13][14] suggested that the haemostatic property of Chromolaena odorata is mostly from the platelet activity/quality rather than quantity or clotting factors. This was further corroborated by the insignificant difference in the PT and PTTK of the test and control groups ruling out significant contributions from clotting factors.…”
Section: Discussionmentioning
confidence: 75%
“…More so, saponnins have been reported to have precipitating and coagulative properties. The result of this study coupled with increased mean platelet volume (MPV) in the aqueous extract and results from previous studies [12][13][14] suggested that the haemostatic property of Chromolaena odorata is mostly from the platelet activity/quality rather than quantity or clotting factors. This was further corroborated by the insignificant difference in the PT and PTTK of the test and control groups ruling out significant contributions from clotting factors.…”
Section: Discussionmentioning
confidence: 75%
“…Crude extracts of plants have been found very useful in ethnomedical practice as part of the process for the treatment of diseases (IWU 1982). In this study, it was shown from the phytochemical studies that there is presence of typical plant constituents (Okoli 2007) such as carbohydrate, calcium, alkaloids, reducing sugar, flavenois, saponins and glycoside, fats and oils, while other constituents such as tanins, resins, terpenoids, acidic compounds, steroids were absent. The acute toxicity study showed that the Canabis sativa extract was non-toxic as shown by the LD 50 (fig 1) of 3000mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Crude extracts of plants have been found very useful in ethnomedical practice as part of the process for the treatment of diseases (Iwu, 1982). In this study, it was shown from the phytochemical studies that there is presence of typical plant constituents (Okoli, 2007) such as calcium, alkaloids, carbohydrates, tannins, saponins, fats, reducing sugar, while other constituents such as resins, terpenoids, acidic compounds, steroids, oil, glycosides were absent. The calcium and alkaloids (protein precipitates) contained in this plant extract are known to be involved in the precipitation of coagulation factors (Taofeeq et al, 2008) which promotes clotting in rats.…”
Section: Discussionmentioning
confidence: 99%